E-BUS PASS MULTI AUTHORITY APPROVAL SYSTEM - M. Madhumitha; R. Sri Swetha; S. Beula Princy (Galaxy International Interdisciplinary Research Journal, 2022)
The project entitled “E-Bus Pass Multi Authority Approval System” is developed using VB.Net as Front end and MS SQL Server as back end. E- Bus Pass Multi Authority Approval System is useful for students who are facing problems with the current manual work of bus pass registration and renewal. The students need to register by submitting their details through application. The HOD will verify the student details and if they are satisfied, they will approve bus pass. The pass will be generated. The student can login with their college Student id and password and then renewal can be performed. This E-Bus Pass Multi Authority Approval System will help candidates to save their time and renewal bus pass without standing in a line for hours near counters. Initially uses need to regist with the application by submitting their details through application. The candidate can login with their student name and password and renewal is performed.